(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Modernism and Positivism constitute two hermeneutic interpretative models that remained popular at the end of 19th Century, and at the beginning of the 20th Century in the Río de la Plata, with specific levels of influence. Both models defined differently the interpretative meanings of Ariel by Jose Rodó, the text analyzed in this article. The primary objective is to identify how each one of these interpretative perspectives works on this discourse.